1974
DOI: 10.1021/bi00705a019
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal denaturation of aqueous staphylococcal enterotoxin B by guanidine hydrochloride, urea, and acid pH

Abstract: The denaturation of staphylococcal enterotoxin B at 23 I : :1" by aqueous guanidine hydrochloride, urea, or dilute HCI was studied by measuring change in the intrinsic viscosity and near-ultraviolet difference spectrum of the protein. Prolonged exposure (hours to days, depending on denaturant concentration) of enterotoxin B to guanidine up to 6 M or urea up to 9 M was required for unfolding to reach equilibrium. Refolding of denatured toxin to native protein after dilution of denaturant was complete within min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The excellent agreement for the amount Staphylococcal enterotoxin B is a bacterial exoprotein which can be purified to molecular homogeneity (Schantz et al, 1965) and is composed of a single polypeptide chain of 239 amino acid residues (Huang and Bergdoll, 1970). The native SEB* 1 molecule in aqueous solution shows an unusual kinetic resistance toward isothermal denaturation by Gdn-HCl or urea, yet appears to be rapidly denatured upon exposure to an acid environment (pH <3.5) in the absence of Gdn-HCl or urea (Warren et al, 1974a). To further elucidate structures of SEB in native and denatured states, a systematic CD study of SEB under a variety of solvent conditions has been performed.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The excellent agreement for the amount Staphylococcal enterotoxin B is a bacterial exoprotein which can be purified to molecular homogeneity (Schantz et al, 1965) and is composed of a single polypeptide chain of 239 amino acid residues (Huang and Bergdoll, 1970). The native SEB* 1 molecule in aqueous solution shows an unusual kinetic resistance toward isothermal denaturation by Gdn-HCl or urea, yet appears to be rapidly denatured upon exposure to an acid environment (pH <3.5) in the absence of Gdn-HCl or urea (Warren et al, 1974a). To further elucidate structures of SEB in native and denatured states, a systematic CD study of SEB under a variety of solvent conditions has been performed.…”
mentioning
confidence: 89%
“…Application of the Chou-Fasman sequence analysis (1974a,b) to SEB indicated that most of the native ß structure is composed of numerous ß segments held in a repeating, antiparallel configuration by intervening ß bends. This highly cooperative (3-sheet configuration probably contributes to the kinetic stability of native SEB toward perturbation by Gdn-HCl or urea (Warren et al, 1974a). Circular dichroism also revealed that disruption of native SEB structure by acid pH resulted in a several-fold increase of a helix and not an increase in the amount of random structure.…”
mentioning
confidence: 90%
“…Culture filtrates of S. aureus 10-275 served as a source of crude SEB. Strain 10-275 is a high-SEB-producing mutant derivative of strain S6 (4,27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Melting curves were recorded at a fixed wavelength of 260 nm. Perecent denaturation was evaluated and the apparent first order rate constant for the thermal denaturation process was calculated as described earlier (13,18).…”
Section: Biochemistryand Molecular Biology Internationalmentioning
confidence: 99%